1996
DOI: 10.1084/jem.183.3.1031
|View full text |Cite
|
Sign up to set email alerts
|

A bcl-2 transgene expressed in hepatocytes protects mice from fulminant liver destruction but not from rapid death induced by anti-Fas antibody injection.

Abstract: SummaryStimulation of the Fas (APO-1, CD95) receptor, which is present on a variety of cells, usually triggers a process of programmed cell death. Systemic injection of anti-Fas antibody into mice leads to fulminant liver destruction resulting from massive hepatocyte apoptosis, and to rapid death. Hepatocytes bear Fas but do not express Bcl-2, a protein that plays, in a number of conditions, a protective role against apoptosis. We have generated mice whose liver expresses Bcl-2 as the result of a bcl-2 transge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
134
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 31 publications
10
134
0
Order By: Relevance
“…Thus, mice with homozygous knockout of Bid, or transgenic overexpression of either BCL-2 or BCL-X L in the liver, showed significantly attenuated Fasmediated hepatitis (Lacronique et al, 1996;Rodriguez et al, 1996;de la Coste et al, 1999a;Yin et al, 1999). The present demonstration of better survival of the liver-specific BRE transgenic mice compared with the non-transgenic littermates in the model is consistent with our previous findings in cell lines showing inhibition of t-BID-induced mitochondrial release of proapoptotic proteins by overexpressed BRE (Li et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, mice with homozygous knockout of Bid, or transgenic overexpression of either BCL-2 or BCL-X L in the liver, showed significantly attenuated Fasmediated hepatitis (Lacronique et al, 1996;Rodriguez et al, 1996;de la Coste et al, 1999a;Yin et al, 1999). The present demonstration of better survival of the liver-specific BRE transgenic mice compared with the non-transgenic littermates in the model is consistent with our previous findings in cell lines showing inhibition of t-BID-induced mitochondrial release of proapoptotic proteins by overexpressed BRE (Li et al, 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Bcl-2/Bcl-X L proteins are thought to act by suppressing release of intra-mitochondrial cytochrome C which, when liberated into the cytosol, activates caspase-9 (and thereafter downstream caspases) via the intermediary adaptor protein Apaf-1 (Li et al, 1997). Indeed, both we (Hueber et al, 1997) and others (Itoh et al, 1993;Rodriguez et al, 1996) have shown that Bcl-2 proteins do suppress CD95-mediated apoptosis in certain circumstances, so Bad might seem a plausible Akt target common to both c-Myc and CD95 apoptotic pathways. However, there is no obvious molecular mechanism linking anti-apoptotic Bcl-2 family members with the classical type 1 CD95/ FADD/caspase-8 pathway.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, crossing of bcl-2 transgenic mice onto the Fas/APO-1 (CD95)-de®cient lpr background revealed that gain of Bcl-2 and loss of Fas/APO-1 (CD95) synergise in promoting lymphocyte accumulation, indicating that these two molecules regulate distinct pathways to lymphocyte apoptosis (Reap et al, 1995;Strasser et al, 1995c). Although in certain cell lines and hepatocytes of transgenic mice, Bcl-2 and certain homologues have been documented to provide some measure of protection ( Figure 6) and (Hashimoto et al, 1991;White et al, 1992;Itoh et al, 1993;JaÈ aÈ ttelaÈ et al, 1995;Lacronique et al, 1996;Rodriguez et al, 1996), the e ects have been modest at best. In our experiments, it is clear that levels of expression that a ord substantial protection, in a dose-dependent manner, against serum deprivation or treatment with staurosporine only weakly inhibited death induced by the Fas/APO-1 (CD95) ligand or TNF (for example, compare data for WEHI-164 cells between Figure 3f to data in Figure 6c, and for SKW6 and CH1 cells in Figure 5).…”
Section: Discussionmentioning
confidence: 99%